Ghouta Timur Pasca Pembebasan Bashar Al-Assad (Kajian Fenomenologi Edmund Husserl) - Fauziyah Kurniawati (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2021)
This research article writing aims to describe East Ghouta post the deliverance of Bashar al-Assad based on the perspective of phenomenology study of Edmund Husserl. The issues to be studied are: (1) how did the East Ghouta conflict start, Syria?; and (2) how is Ghouta Timur after the release of Bashar al-Assad ?. The object under study is the national and international online news media. The research method used is qualitative method. Data collection is used with watch and note techniques. Data analysis technique used is descriptive analysis technique. To test the validity of data, the technique used is triangulation technique. The results of this study are: (1) East Ghouta conflicts, Syria started on March 15, 2011. In addition to the background of the Arab Spring events, it turns out the level of emotionality of the President, Bashar al-Assad is quite lit whenever there is something that is not in his heart, which eventually led to hundreds of thousands of civilian lives lost and millions more fled; and (2) after 6 years of slipping into a totally inhumane empire, Ghouta were finally freed from the shackles of their own warden by Bashar al-Assad.Keywords - East Ghouta, deliverance, Bashar al-Assad, phenomenology